Valerius Flaccus, Argonautica, Book I : a commentary - Kleywegt, A. J. (Mnemosyne, Supplements, 2005)
This work provides a full commentary on the first book of Valerius Flaccus' Argonautica , an epic which has received increased attention in the last few decades, as may be seen from two recent editions (1997 and 2003). Its first aim is to clarify the text, which is sometimes rather difficult and, in places, still not established with certainty. Apart from this philological aspect, the literary merits of the poem have also been taken into account.